2000
DOI: 10.1016/s0886-3350(00)00367-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power calculations in patients with extreme myopia

Abstract: In eyes with axial lengths longer than or equal to 27.0 mm, current third- and fourth-generation lens calculation formulas have a tendency to over minus patients between -1.0 and -4.0 D. The formulas appear to perform better for plus-power IOL implantation than for minus-power IOL implantation. The use of B-scan ultrasonography to locate posterior pole staphylomas may improve the accuracy of IOL calculations in eyes with extreme myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
1
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 9 publications
3
63
1
11
Order By: Relevance
“…Many studies reported that the SRK/T formula, which we used for IOL power calculation, is appropriate for biometry in high myopia of ≥27mm axial length. 2, 8, 10 Zaldivar et al 11 reported that 92% of eyes were within ±1.0D when using SRK/T, and concluded that in eyes with axial lengths ≥ 27.0 mm, current third-and fourth-generation lens calculation formulas have a tendency to over minus patients between -1.0 and -4.0 D, leaving patients with postoperative hyperopia. Similarly, Tsang et al 2 found that SRK/T formula showed a slight tendency toward resultant hyperopia, resulting in a postoperative hyperopic refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that the SRK/T formula, which we used for IOL power calculation, is appropriate for biometry in high myopia of ≥27mm axial length. 2, 8, 10 Zaldivar et al 11 reported that 92% of eyes were within ±1.0D when using SRK/T, and concluded that in eyes with axial lengths ≥ 27.0 mm, current third-and fourth-generation lens calculation formulas have a tendency to over minus patients between -1.0 and -4.0 D, leaving patients with postoperative hyperopia. Similarly, Tsang et al 2 found that SRK/T formula showed a slight tendency toward resultant hyperopia, resulting in a postoperative hyperopic refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of SRK-T, Hoffer Q, Holladay 1 and Holladay 2 formulae in eyes with axial lengths longer than or equal to 27.0mm was assessed by Zaldivar et al 6 It was concluded that current third-and fourth-generation lens calculation formulae have a tendency to over minus patients between −1.0 and −4.0 D. The formulae appear to perform better for plus-power IOL implantation than for minus-power IOL implantation. Wang JK, et al 7 concluded IOL power calculated using the Haigis formula predicted the best refractive outcome in long eyes.…”
Section: Age 43 To 69 Yearsmentioning
confidence: 99%
“…Die SRK-T-Formel ist eine etablierte Methode zur Biometrie bei Patienten mit hoher Achsenmyopie und hinsichtlich refraktiver Ergebnisse der Haigis-oder Holladay-1-Formel ähnlich [11,15,18,20]. Haigis [4] hat aber kürzlich die Bedeutung unterschiedlicher A-Konstanten für Positiv-Dioptrien-und Negativ-Dioptrien-IOLs hervorgehoben.…”
Section: Diskussionunclassified